Reaching a Foreign Audience: Cultural Transfers in Audiovisual Translation - Nathalie Ramière (JoSTrans: The Journal of Specialised Translation)
This paper examines some of the issues involved in the intercultural transfer of films. It focuses on the translation of culture-specific references and questions in particular the validity of the notions of foreignisation and domestication, brought to the fore of Translation Studies by Venuti (1995), as a conceptual framework traditionally used to discuss the strategies applied when translating cultural specifics. Drawing on the findings of a pilot study consisting of three French films dubbed and subtitled into English, this paper suggests a theoretical challenge by proposing a more pragmatic approach to the study of cultural transfer in audiovisual translation (AVT). More particularly, it will examine whether it is possible to observe any form of consistency in the strategies used for the translation of culturally-bound references and what this implies for the dialogic relationship between Self and Other, and the representation of alterity.